Effect of Adding Nano-Materials and Carbon Fiber on Impact Strength of Cementitious Composite (CC) - Raouf, Zain El-Abdin; Al-Suhaili, Rafia H.; Mahdi, Zainab H. (Al-Nahrain Journal for Engineering Sciences, 2017)
This study involves the addition of nano silica (NS) with average particle size 12nm, micro high reactivity mitakaaolin (MHRM) particle size ? 0.554 ? 1.271 µm, micro ground granulated blast-furnace slag (MGGBFS) particle size ? 0.365 <2.932 µm and micro carbon fibers, the length of the fiber 8.5 mm and a diameter of 0.001 mm to cementations mixtures to investigate their effect on the impact strength with used magnetic water or normal water in mixing blends. The results have shown that cementitious mixtures used in the mixing magnetic water containing 10% MGGBFS, 10% MHRM or 2.5% NS and reinforced with 2% micro carbon fiber have improved greatly in impact strength as the absorbed energy to the emergence of the first crack at age 28 days reaches to (231.55, 209.49 and 199.49) kN.m respectively, whereas for the reference cementitious mixtures it has been 1.574 kN.m